ISLAM AND ARTIFICIAL INTELLIGENCE: Perspectives from Traditionalist and Modernist Muslim Communities in Indonesia - Firdaus, Muhammad Anang; Syihabuddin, Muhammad; Fuady, Zein (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2025)
This study explores how traditionalist and modernist Muslim communities in Indonesia respond to the ethical, religious, and social implications of Artificial Intelligence (AI). Using a qualitative analysis of fatwas, religious texts, and scholarly discourse, the research identifies distinct approaches: traditionalists prioritize doctrinal continuity and exhibit caution, while modernists adopt more adaptive interpretations that seek to align AI with Islamic ethical principles. Despite methodological differences, both groups express shared concerns regarding AI’s influence on human agency, moral responsibility, and religious authority, while also recognizing its potential benefits when guided by Islamic values. The findings reveal that theological orientation alone does not shape responses to AI; socio-cultural factors also significantly influence how religious communities interpret emerging technologies. This study offers a nuanced perspective on how Indonesian Muslims navigate the intersection of faith, ethics, and technological advancement, contributing to broader discussions on Islamic thought and digital transformation in contemporary society.